Design and fabrication of an eco-friendly cleaning machine / Nur Aliah Azmi - Azmi, Nur Aliah (2024)
The eco-friendly cleaning machine project is aware of the significance of consumer acceptance and market need. It considers how people, companies, and organizations are becoming more aware of and interested in sustainable cleaning options. The project aims to speed the shift to ecologically friendly cleaning practices by creating eco-friendly cleaning equipment that is affordable, user-friendly, and meets market expectations.in, eco cleaning machine can helps the cleaning staff that have the experience back pain issues because of the employment. Understanding and improving the interaction between humans and cleaning machines is another knowledge gap. Research is needed to design user-friendly interfaces and intuitive controls that make operating cleaning machines more accessible and efficient. Studying the safety and ergonomics of utilizing cleaning machines can also reduce the risk of injuries while improving the user's experience. The manually operated eco-friendly cleaning machine did not require a motor or fuel in this project. Using SolidWorks, the eco-friendly cleaning machine may be created. As suggested by the project's name, an eco-friendly cleaning machine prototype will be what is expected as a final product. The efficiency of the eco-friendly cleaning machine in sweeping the surface and its ability to avoid back pain will be evaluated.